2020
DOI: 10.5999/aps.2020.00108
|View full text |Cite
|
Sign up to set email alerts
|

Breast implant-associated anaplastic large cell lymphoma in an Asian patient: The first case report from Thailand

Abstract: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) has received increasing interest among plastic surgeons as a long-term complication of breast augmentation. Although the prognosis is usually good, mortality is a possible outcome. Most of the cases reported in the past two decades have been from the United States, Europe, and Australia, whereas cases of BIA-ALCL in Asia remain rare. Herein, we describe the first known case of BIA-ALCL in Thailand, in which a 32-year-old woman developed BIA-AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…The cosmetic industry in Asia, including Korea, has undergone recent growth along with an expansion in breast implant surgery. 3 Although the incidence of BIA-ALCL in Asia has been low, recent reports of BIA-ALCL are emerging in Asia, including Japan 11 and Thailand 12 ( Table 1 ). In August 2019, the first Korean BIA-ALCL case was officially announced by the Ministry of Food and Drug Safety and the Korean Society of Plastic and Reconstructive Surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The cosmetic industry in Asia, including Korea, has undergone recent growth along with an expansion in breast implant surgery. 3 Although the incidence of BIA-ALCL in Asia has been low, recent reports of BIA-ALCL are emerging in Asia, including Japan 11 and Thailand 12 ( Table 1 ). In August 2019, the first Korean BIA-ALCL case was officially announced by the Ministry of Food and Drug Safety and the Korean Society of Plastic and Reconstructive Surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was a 67-year-old Japanese woman with breast cancer (BC) who underwent mastectomy and reconstruction with a textured silicone breast implant in 2002 and unfortunately developed ALCL in 2018. The first known case of BIA-ALCL in Thailand was a 32-year-old woman who developed BIA-ALCL after using a textured implant for breast augmentation for 3 years (19). Kim et al reported the first case of BIA-ALCL in South Korea which showed a typically delayed seroma around the implant 7 years after the implantation of a textured implant (20).…”
Section: Epidemiologymentioning
confidence: 99%
“…For stage IIA-IV disease, systemic treatments are required including radiotherapy, chemotherapy and the administration of immunotherapeutic agents such as BV. For patients with invasion beyond the fibrous capsule (stage IIA), successful treatment outcomes have been achieved with full capsulectomy in combination with radiotherapy 64 or chemotherapy and radiotherapy 65 , 66 , 67 . The successful use of BV has been reported when a patient progressed through chemotherapy 65 and prior to capsulectomy, in order to avoid more complicated and risky surgery involving the sub-pectoral muscles and ribs.…”
Section: Breast Implant-associated Lymphomamentioning
confidence: 99%
“… 73 , 74 As of May 2021, there were 994 BIA-ALCL cases and 37 BIA-ALCL-related deaths reported worldwide, 75 including cases seen for the first time in Thailand, Japan and Taiwan. 67 , 76 , 77 However, this is likely an underestimation and it is possible that many cases have gone undiagnosed once the disease is disseminated and/or are not reported, perhaps more recently due to the COVID-19 pandemic. In this vein, the total number of BIA-ALCL cases worldwide is difficult to determine due to (i) a lack of information regarding the number of people with breast implants in situ and (ii) a limited awareness of BIA-ALCL by surgeons and patients leading to large discrepancies in the reporting of cases.…”
Section: Breast Implant-associated Lymphomamentioning
confidence: 99%